Development of a Web-Based Indonesian Super Priority Tourism Promotion Media Website - Tri Agus Setiawan; Dedi Gunawan; Untung Suropati (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Indonesia has a variety of natural attractions, which can be by Indonesians or foreigners. By 2023, Indonesia's tourism industry could contribute about US$10 billion in national currency. The position is number four after oil, coal and palm coconut. According to data from PDTT Indonesia has a total of 7,275 tourist villages spread across the province. With the creation of this website showed several destinations of different islands that have their own characteristics of each of its regions.Information technology provides a container of information for people who want to know more about super priority tourist destinations in Indonesia spread from the west to the east of Indonesia, as well as such destinations as borobudur temple, toba lake, likupang, mandalika, and also labuhan bajo. Super Priority Tourist Destinations are part of an Indonesian government program aimed at developing top tourist destinations in various regions, based on data on the most frequently visited destinations by tourists from both the country and abroad. Super-priority tourist destinations are made not only to increase visits to such tours, but also to improve the well-being of local communities. With the creation of this website, a wide selection of places is provided so that visitors can choose the tourist destination to visit first by seeing how the place to facilitate the travel plan. The research method used for the success of this website is the waterfall method, with this method developed this super priority travel website using wordpress with a periodic and sequential editing system from top to bottom.